Ecological performance analysis of an endoreversible regenerative Brayton heat-engine - Ust, Y; Safa, A; Sahin, B (ELSEVIER SCI LTD, 2005)
A performance analysis based on an ecological performance criterion has been performed for an endoreversible regenerative Brayton heat-engine. In the model, the heat-transfer irreversibilities were considered and other irreversibilities were neglected. The ecologic objective-function, defined as the power output minus the loss rate of availability is taken as the optimization criterion. The optimum performance parameters that maximize the ecological objective function are investigated. The effect of the regenerator effectiveness on the global and optimal performance have been discussed. The results obtained are compared with those of the maximum-power criterion. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Brayton heat engine; ecological optimization; regenerator effectiveness; MAXIMUM POWER-DENSITY; ENTROPY GENERATION MINIMIZATION; OPTIMIZATION CRITERION; EFFICIENCY; THERMODYNAMICS; Energy & Fuels; Engineering